It all adds up : the story of people and mathematics - Launay, Mickael (. - London : William Collins, 2018)
From our ability to calculate the passing of time to the algorithms that control computers and much else in our lives, numbers are everywhere. They are so indispensable that we forget how fundamental they are to our way of life. Mickaël Launay mixes history and anecdotes from around the world to reveal how mathematics became pivotal to the story of humankind. It is a journey into numbers with Launay as a guide. In museums, monuments or train stations, he uses the objects around us to explain what art can reveal about geometry, how Babylonian scholars developed one of the first complex written languages, and how Arabic numbers were adopted from India. "It All Adds Up" also tells the story of how mapping the trajectory of an eclipse has helped to trace the precise day of one of the oldest battles in history, how the course of the modern-day Greenwich Meridian was established, and why negative numbers were accepted just last century.
Includes bibliographical references (pages 244-248) and index.
Keywords: Mathematics -- Popular works; Mathematics